Transport Organization and its Corporate Identity - Bielikova, Alžbeta (Promet - Traffic&Transportation, 2006)
The article deals with the corporate identity and its parts intransport organization. The corporate identity is a strategicallyarranged idea based on the firm’s philosophy, firm’s vision andlong-term business aim. It must be confirmed by the firm’s behaviourand its internal and external communication.